ChatGPT in the classroom: Exploring student attitudes and ethical concerns around AI-assisted learning - Zhou, Gongliang (Edelweiss Applied Science and Technology, 2025)
This study investigates undergraduate students’ perceptions of ChatGPT in higher education, with a particular emphasis on its perceived benefits and ethical challenges. Guided by the Technology Acceptance Model and Ethical Decision-Making Theory, the research adopted a qualitative exploratory design. Data were collected through semi-structured interviews with 20 undergraduate students from a public university in China, selected through purposive sampling. Thematic analysis was conducted using Braun and Clarke’s six-phase framework. Findings revealed four major themes: perceived benefits, concerns and limitations, ethical considerations, and institutional and AI literacy gaps. While students appreciated ChatGPT for enhancing academic efficiency, offering cognitive support, and promoting independent learning, they also expressed concerns regarding overreliance, diminished critical thinking, AI accuracy, and ethical ambiguities—particularly in relation to plagiarism and data privacy. Additionally, students highlighted a lack of institutional guidance and inconsistent faculty attitudes, which contributed to confusion about appropriate AI use. The study concludes that ChatGPT functions as both a valuable academic aid and a potential risk to academic integrity and student autonomy. Practical implications include the urgent need for clear institutional policies, faculty training, and AI literacy programs to ensure ethical, informed, and effective integration of AI tools in educational settings.